A revision of Calodera Mannerheim. II. A new species, new synonyms, and additional records (Coleoptera: Staphylinidae: Aleocharinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2003)
Based on material that has become available since the first part of the revision, various new records of Calodera species are presented. C. zerchei sp. n., the first species from the Russian Far East, is described and distinguished from C. desdemona Sharp, a species recorded only from Japan. The following synonymies are proposed: Calodera Mannerheim, 1830 = Ityocara Thomson, 1867, syn. n.; Calodera aethiops (Gravenhorst, 1802) = Aleochara (Calodera) perspicua Gistel, 1857, syn. n. Calodera rubens Erichson, the type species of Ityocara, is transferred to Calodera again. The sexual characters of Calodera rubens, C. desdemona, and C. zerchei are illustrated. In the Holarctic region, 17 species of Calodera are recognized, 11 of them Western Palaearctic, 3 Eastern Palaearctic, and 3 Nearctic. So far all the species from other regions which were previously attributed to Calodera and which have been (re-)examined have proved to belong to other genera, which suggests that Calodera is a Holarctic genus.KeywordsColeoptera, Staphylinidae, Aleocharinae, Oxypodini, Calodera, Palaearctic region, taxonomy, new species, new synonyms, new combination, new records.Nomenclatural Actsperspicua Gistel, 1857 (Aleochara (Calodera)), syn. n. of Calodera aethiops (Gravenhorst, 1802)zerchei Assing, 2003 (Calodera), spec. n.